On Not Operationalizing Disability in Theology - Capretto, Peter (Journal of the American Academy of Religion, 2017)
Informed by debates on the reductionism of defining disciplinary concepts in disability studies and religion, this article argues that theology faces a unique ethical and methodological challenge in whether to operationalize experiences with disability into anything theologically significant or useful. Analyzing how some scholarship in disability theology has problematically appropriated disability even for liberatory purposes, it contends that theology struggles methodologically to distinguish itself from ideological rhetoric that deliberately marginalizes persons with disability. However, rejecting operationalization not only threatens the collaboration between theology and the social sciences afforded by operationalizing shared inquiries, but risks suggesting that disability is not worthy of sustained theological attention. The article proposes that this double-bind forces theology to critique operationalization by scrutinizing its relationship to usefulness itself. This means resisting the methodological compulsion for all persons and things to become useful, and retaining the theological possibility that interpersonal experience—disabled and otherwise—may be useless.